The psychology of conspiracy theories - Prooijen, Jan-Willem van 1975- (London New York Routledge, 2018)
Cover -- Title -- Copyright -- CONTENTS -- Preface -- 1 Psychology of conspiracy theories -- 2 When do people believe conspiracy theories? -- 3 The architecture of belief -- 4 The social roots of conspiracy theories -- 5 Conspiracy theories and ideology -- 6 Explaining and reducing conspiracy theories -- Further reading -- Notes -- References